Tantangan Kontemporer Pengembangan Sumber Daya Manusia Koperasi Industrial - Siti Rosmayati (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
In a competitive environment, employees of every organization are a key factor in business success. In various fields such as health, education, media, banking insurance, etc. Human resources play an important role in successful service delivery. Most service industries emphasize the absorption of human resources with the necessary qualifications, expertise, and practical basic training. However, the Cooperative does not have this privilege due to its current structure and functions. Cooperatives began to enter and develop in Indonesia. In Indonesia cooperatives were introduced by Patih R.Aria Wiria Atmaja in 1896. They have increasingly complex business mechanisms that require all modern management tools and techniques to succeed, but one of the obstacles to their growth is the lack of qualified personnel to manage business management in effective field. Recruiting, training, retaining the existing workforce and cultivating a culture of continuous learning are some of the challenges facing Cooperatives even today. Because the development of human resources (HR) is a key factor that determines the characteristics of a successful institution. Cooperatives also need to develop permanent members, management and especially employees. Therefore, in this study, an attempt was made to signal the need for HRD and identify contemporary challenges in the implementation of HRD activities in cooperatives.